2015
DOI: 10.1007/s10336-015-1182-9
|View full text |Cite
|
Sign up to set email alerts
|

To fledge or not to fledge: factors influencing the number of eggs and the eggs-to-fledglings rate in White Storks Ciconia ciconia in an agricultural environment

Abstract: Numerous studies have explored the relationship between environmental factors and White Stork Ciconia ciconia reproduction, mainly expressing breeding success as the number of fledglings. Nonetheless, one of the most critical life-history stages in birds falls between egg-laying and fledging, and identifying the factors causing offspring mortality during this period provides valuable knowledge. We quantified the number of laid White Stork eggs and the proportion of eggs that turned into fledglings in an agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 107 publications
(143 reference statements)
0
2
0
Order By: Relevance
“…Nesting on trees was nearly abandoned in 2015-2016 with only 0.6%, while nesting on hay bales and stacks was completely abandoned. The first White Stork census found that 37.2% of the nests were placed on trees and 7.52% on hay bales (Jovani & Tella 2004;Denac 2006;Hilgartner et al 2014;Eggers et al 2015) and distance to the main feeding areas (Hilgartner et al 2014;Djerdali et al 2016a) are known to affect the breeding parameters, as is the combination of the en-vironmental factors with colony size (Janiszewski et al 2014;Djerdali et al 2016b), sometimes resulting with density-dependent brood reduction (Zurell et al 2015). These factors might be behind the observed differences in the breeding parameters among some regions in North Macedonia in 2015, but clear correlation between breeding densities and breeding parameters is lacking (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…Nesting on trees was nearly abandoned in 2015-2016 with only 0.6%, while nesting on hay bales and stacks was completely abandoned. The first White Stork census found that 37.2% of the nests were placed on trees and 7.52% on hay bales (Jovani & Tella 2004;Denac 2006;Hilgartner et al 2014;Eggers et al 2015) and distance to the main feeding areas (Hilgartner et al 2014;Djerdali et al 2016a) are known to affect the breeding parameters, as is the combination of the en-vironmental factors with colony size (Janiszewski et al 2014;Djerdali et al 2016b), sometimes resulting with density-dependent brood reduction (Zurell et al 2015). These factors might be behind the observed differences in the breeding parameters among some regions in North Macedonia in 2015, but clear correlation between breeding densities and breeding parameters is lacking (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…Project EVE enables lifecycle management and remote orchestration of any application and hardware, and incorporates a zero-trust security model. Fledge [53] Scalable and secure IIoT open-source platform for building and operating industrial applications for condition monitoring, predictive maintenance, increased ef iciency (Overall Equipment Effectiveness, or OEE), higher quality, situation awareness, and safety. Home Edge [54] Edge computing open-source framework, platform, and ecosystem that provides an interoperable, lexible, and scalable edge orchestration and computing services platform, with APIs that can also be used with libraries and runtimes to enable various user scenarios for the home.…”
Section: Future Research Directionsmentioning
confidence: 99%